Estimation of the orientation of stress in the Earth’s crust without earthquake or borehole data - Andrew A. Delorey (Nature Portfolio, 2021)
The orientation of maximum horizontal compressive stress in the crust can be estimated in regions lacking borehole or earthquake source data through the use of ambient Earth noise to measure stress-induced anisotropy of nonlinear anelastic behavior.